Sistematización del proceso de creación de la comparsa “Un rey de quién sabe dónde” del curso carnaval 2021-II (2024)
This work gives an account of the systematization of the artistic-pedagogical practice from the artist in training, based on her experience through the Carnaval subjet during the 2021-II, at the Bachelor's Degree in Artistic Education with emphasis on Dance and Theater of the University Antonio Narino, Bogotá. In this study, a reflection is made on the process of interdisciplinary and collective creation of the Comparsa “A King from Who Knows Where” socialized in the “Galería San Cristóbal Festiva” festival, and which constituted the final exhibition of the semester.